PELATIHAN PEMBUATAN MI SINGKONG DI GEREJA ST. IGNATIUS LOYOLA, SEMPLAK, BOGOR [TRAINING OF CASSAVA NOODLE MAKING AT ST. IGNATIUS LOYOLA CHURCH, SEMPLAK, BOGOR] - Nuri Arum Anugrahati; Adolf J.N. Parhusip (Jurnal Sinergitas PKM & CSR, 2018)
Until now the production of noodles still depend on the availability of wheat flour as on of the ingredients. Cassava can be utilized as an alternative to subtitute the wheat flour in noodle making. This is the underlying of community services of Food Technology Department on August 10, 2017. This community service aimed to provide training of cassava noodle making on Catholic Church St. Ignatius Loyola, Semplak, Bogor, West Java. The questionnaire result showed that 96% of participants can participate in the training well and they are interested practicing the making of noodles into productive and independent business.